Leflunomide in the Treatment of a Pseudotumoral Genital Herpes Simplex Virus Infection in an HIV Patient - Marie R. Roger; Gregory M. Anstead (Case Reports in Infectious Diseases)
The patient is a 52-year-old African American man with a past medical history of HIV infection (on antiretroviral therapy, CD4 count 399 cells/µL, and undetectable HIV viral load) and recurrent genital herpes. While on valacyclovir, the patient presented with four tumorous lesions on the perineum and scrotum. A biopsy specimen stained positively with HSV-1 and HSV-2 immunostains and displayed a lymphoplasmacytic infiltrate. The patient received foscarnet and imiquimod for two weeks with minimal improvement. Based on the previous activity of leflunomide, which has both antiviral and immunomodulatory properties, in cytomegalovirus and herpes simplex infections, leflunomide 20 mg orally twice daily was started. The patient received 23 days of foscarnet, 14 days of topical imiquimod, and 11 days of leflunomide with approximately 80% reduction in the size of the perineal lesion. After nine months on leflunomide there was complete regression of the large perineal lesion and only two small ulcerations remained on the scrotum. Pseudotumoral herpes lesions in HIV patients represent an immune reconstitution event and are poorly responsive to the usual anti-herpes agents. This report demonstrates the successful use of leflunomide in the treatment of an HIV patient with pseudotumoral herpes. Thalidomide has also been used with some success.